Análise da Classificação Decimal Universal (CDU) e os esforços que estão sendo realizados para a sua transformação em linguagem universal de informação científica - Oliveira, Regina Maria Soares de (1977)
Study of the possibility of transforming UDC in a future universal language for scientific information. Analysis of this reform, partly based on proposals presented to FID by its Committees. Emphasis was given to the structural roots of UDC, as well as to its rich contents which can be utilized in its reformulation.